Metode Role play Meningkatkan Pengetahuan dan Tindakan Pertolongan Pertama Luka Pada Anak Usia Sekolah Dasar di Daerah Rawan Bencana - Wirahadi Saputra; Ilya Krisnana; Iqlima Dwi Kurnia; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2019)
Introduction: Knowledge and skill of school age children is still lack about first aid of wound. The purpose of this study was to determine the effect of role play methodtowards knowledge and wound first aid skill on student. The aim of experiment is to study the effect of role play method towards knowledge and wound first aid skill on student.Methods: The design used in this study was quasi-experimental quasi-eksperimental pretest-posttest control group design. The samples were gathered using simple random sampling method consisted of 50 students based on the inclusion criteria which were divided into experimental and control groups. The independent variable was  health education using role play methods and the dependent variables were knowledge and first aid wound skill. The data were analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with level significance α<0,05.Results: The Wilcoxon Signed Rank Test results showed that there were enhancement for knowledge (p=0.000) and first aid wound skill(p=0.000) for post intervention toward the experimental group. These data were strengthened by the result of Mann Whitney U Test statistical analysis that showed the significant differences for knowledge (p=0.000) and action application of open wounds care (p=0.000).Conclusion: It can be concluded that health education using role play methods affected knowledge and wound first aid skill on student. The suggestion for the further experiment is to compare role play methods with other health education methods to find out effective methods of health education for student.